Perceptions and experiences of women and providers on barriers and facilitators of quality emergency obstetric and newborn care services in public hospitals of West Shoa Zone, Oromia, Ethiopia: A phenomenological qualitative study - Tolera Gudissa Damme; Sileshi Garoma Abeya; Dereje Bayissa Demissie (PLoS ONE, 2026)
Background Evidence shows that health care delivery is inadequate and poor quality in low- and middle-income countries. Recently, poor quality of health care has been a more significant challenge for reducing maternal and perinatal mortality than insufficient access to health care services. However, data on barriers and facilitators to quality emergency obstetric and newborn care service in Ethiopia are limited. Therefore, this study aims to explore the perceptions and experiences of women and providers on barriers and facilitators of quality emergency obstetric and newborn care services in public hospitals of West Shoa Zone, Ethiopia. Methods A phenomenological qualitative study was conducted in four selected public hospitals of West Shoa Zone from June 01 to July 30 of 2024. A total of sixty-five study participants were purposively selected and interviewed until data saturation. The data were collected through focus group discussions (38 participants), in-depth interviews (12 participants), and key informant interviews (15 participants). The collected data were transcribed verbatim and translated into English language. Finally, MAXQDA software version 24.4.1 was used for thematic data analysis. Results The study findings were categorized into two major themes (i.e., barriers and facilitators) and three sub-themes (factors related to health care facilities, factors related to health care providers, and factors related to clients and the community as a whole). The main identified barriers were a shortage of medical resources and facility infrastructures; insufficient human resources; knowledge and skill gaps of health care providers; inadequate respectful maternity care; a weak client referral system; a lack of updated training; limited community awareness on emergency cases; and inadequate mentoring and supervision activities. In contrast, the major facilitators included the availability of free maternity services, a multidisciplinary team, strong provider commitment and teamwork, establishment of neonatal intensive care units and blood banks, access to ambulances, and community pharmacies. Conclusions This study identified a range of barriers and facilitators influencing the quality of emergency obstetric and newborn care services, encompassing factors related to healthcare facilities, healthcare providers, as well as clients and the whole community. Therefore, all health care facilities and the regional health bureau need to improve the identified barriers and strengthen all facilitators of quality emergency obstetric and newborn care services.